Burnout and academic satisfaction of nursing students in traditional and integrated curricula - Rafaely da Silva Batista; Márcio Souza dos Santos; Emiliana Cristina Melo; Ricardo Castanho Moreira; Júlia Trevisan Martins; Maria José Quina Galdino
ABSTRACT Objective: To verify the prevalence of burnout and its relationship with the academic satisfaction of nursing students in traditional and integrated curricula. Method: Quantitative, observational, cross-sectional, and analytical descriptive study with nursing undergraduates in two public universities. The data were collected in the classroom through a characterization survey, Maslach Burnout Inventory, and the Nursing Student Satisfaction Scale, and analyzed through inferential and descriptive statistics. Results: The participants included 301 undergraduate students. The prevalence of burnout in the traditional curriculum was 30.2%; in the integrated one, this was 16.2%. Academic efficacy (p=0.004), satisfaction with curriculum and teaching (p=0.011), and professional and social integration (p<0.001) were higher for students in the integrated curriculum. Satisfaction with the educational environment was higher in the traditional curriculum (p=0.012). Burnout was statistically associated with low academic satisfaction in all dimensions. Conclusion: The prevalence of burnout has differed significantly among students in the analyzed curriculum models and is directly associated with academic satisfaction or lack thereof. Educators should develop preventive actions against burnout in future nurses focusing on the promotion of academic satisfaction.